Aplicación de índices de estado trófico en el embalse de Salto Grande - Crettaz Minaglia, Melina Celeste (2013)
Eutrophication is the process by which nutrients, mainly phosphorus, are contributed. Currently, this has increased due to human activity and population growth which has caused the deterioration of water quality and limited its potential uses. In this study, the trophic state of the Salto Grande Reservoir was determined in the stretch between Monte Caseros/Bella Union and the dam, during the summer period of 2010 through the application of different indices. Moreover, the representative blue green algae from the area corresponding to the genera Microcystis and Dolichospermum and their relation to the nutrients were studied. Nutrient concentrations, mainly phosphorus, were relatively high, determining an eutrophic state from the area of study. Due to the flooding which began in November 2009, the relative abundance of cyanobacteria was not high, with a maximum of approximately 40,000 cells/ml. Furthermore, no linear correlation was established between cyanobacteria and the nutrients studied. We conclude that, as suggested by the records, nutrients would not be a limiting factor for the proliferation of cyanobacteria in the reservoir area of Salto Grande.